2012
DOI: 10.1371/journal.pone.0033522
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Shock Mediated Overexpression of HNF1β Mutations Has Differential Effects on Gene Expression in the Xenopus Pronephric Kidney

Abstract: The transcription factor HNF1B, encoded by the TCF2 gene, plays an important role in the organogenesis of vertebrates. In humans, heterozygous mutations of HNF1B are associated with several diseases, such as pancreatic β-cell dysfunction leading to maturity-onset diabetes of the young (MODY5), defective kidney development, disturbed liver function, pancreas atrophy, and malformations of the genital tract. The African claw frog Xenopus laevis is an excellent model to study the processes involved in embryogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…In contrast to these observations, the overexpression of two human HNF1B mutants in Xenopus embryos has recently been shown to result in modest effects on pronephros development, although proximal tubules were the most affected (Sauert et al, 2012). Since the mutants employed in that study either retained transcriptional activity (P328L329del) or did not bind DNA (A263insGG), it is likely that they were less efficient than our construct in decreasing Hnf1b activity.…”
Section: Research Articlementioning
confidence: 57%
“…In contrast to these observations, the overexpression of two human HNF1B mutants in Xenopus embryos has recently been shown to result in modest effects on pronephros development, although proximal tubules were the most affected (Sauert et al, 2012). Since the mutants employed in that study either retained transcriptional activity (P328L329del) or did not bind DNA (A263insGG), it is likely that they were less efficient than our construct in decreasing Hnf1b activity.…”
Section: Research Articlementioning
confidence: 57%
“…40,43 Experiments in frogs have further implicated Hnf1b factors in nephron formation but determining their precise function has been elusive. 36,44,45 Here, using the zebrafish model, we demonstrate that Hnf1b factors act downstream of pax2a and pax8 to restrict podocyte fate and to establish the proximo-distal segmentation pattern of the nephron ( Figure 7). In addition, evidence for transcriptional regulatory loops was identified between hnf1ba/b, pax2a, pax8, and irx3b.…”
Section: Discussionmentioning
confidence: 76%
“…Heterodimer of rBAT and BAT1 (b 0,+ AT), which is coded by SLC7A9 , transports cystine and dibasic amino acids, such as lysine, arginine, and ornithine, and thus is critical for reabsorption of these amino acids in the proximal tubule. With regard to the relation of HNF1β and rBAT, Sauert K. et al reported that HNF1β mutation decreased rBAT expression [ 46 ]. And the results of our metabolome analysis that intracellular lysine, arginine, and ornithine were significantly higher in HNF1β-high cells ( Fig.…”
Section: Discussionmentioning
confidence: 99%